ASSESSMENT OF VITAMIN D DEFICIENCY PREVALENCE IN ADULTS WITH CHRONIC FATIGUE SYNDROME: A CROSS-SECTIONAL STUDY - Dr. Rahul Vasudeo Jawale , Dr. Ankur Anil Jhavar, Dr. Ashish Sanjay Sarode , Dr. Dilip Onkar Patil, Dr. Dinesh Eknath Nehete, Dr. Chetan Bhagwat Chaudhari, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Chronic Fatigue Syndrome (CFS) is a complex disorder characterized by extremefatigue that does not improve with rest and may worsen with physical or mental activity. Recentstudies suggest a potential link between Vitamin D deficiency and the severity of symptoms experienced by CFS patients.